Implementasi Model Make A Match untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SD Eka Tjipta Mandang Seruyan - Muryanto, Deddy; Anjarwani, Ratih (Universitas Muhammadiyah Kuningan, 2025)
This research aims to determine the learning outcomes of the make a match type cooperative learning model on student learning outcomes on temperature and heat material in class V semester II of SD Eka Tjipta Mandang Seruyan. This research is classroom action research (PTK) with the research subjects being class V students at SD Eka Tjipta. Data collection techniques through science learning tests. The test consists of 10 multiple choice questions and 5 essay questions. Analysis is obtained through observation and tests. Based on the results of observations, it shows that out of 41 students, 24 students were still below the KKM in Class V SD Eka Tjipta Mandang Seruyan, 24 students were below the KKM with a class average score of 59.27. The results of the research show that the make a match type cooperative learning model is effective in improving cycle 1 science learning outcomes, showing a student learning completion level of 68% with an average score of 70.61. In cycle 2, the level of completeness of student learning outcomes was 95% with an average score of 87.88. This research proves that the application of the make a match type cooperative learning model can improve science learning outcomes in class V at SD II Eka Tjipta Mandang Seruyan.